Analysis of Factors Related to Low Back Pain Among Salt Farmers in Oebobo Village, Kupang District - Marini Novita Landutana; Luh Putu Rulianti; Agus Setyobudi (Universitas Nusa Cendana, 2022)
Low back pain is a pain felt in the lower back area, between the lower ribs corner and sacrum. In Indonesia, low back pain data is not known for sure but is estimated at 37% - 76% of the total population in Indonesia. The health profile of Kupang City in 2018 showed that connective ligature disease ranks 6th out of the 10 most diseases that happened in Kupang city with a total of 12.756 cases having a percentage of 7,3% of the total population in Kupang city. The risk factor of low back pain is individual, job, and environment. This research aims to analyze the risk associated with low back pain complaints among salt farmers in Oebelo Village, Kupang Regency. This research used observational analytics with a cross-sectional study design. The population for this research was 54 people and the sample was 48 people. The sampling technique that using in this research is simple random sampling. Data analysis using chi-square with a significance level of a=0.05. The result showed that the risk of low back pain increased by risky age (p=0,002), over the working period (p=0,002), non-ergonomic working attitude (p=0,000), and over working hours (p=0,000). Workers should pay attention to low back pain causes and symptoms that appear.